SELF-CONFIDENCE FOR PERSONS WITH PHYSICAL DISABILITIES IN SENTRA BUDI PERKASA PALEMBANG THROUGH ISLAMIC PSYCHOTRAPHY APPROACH - Adela Zinta Sari; Kamila Istakhana; Sinar Saprini; Ardiansyah; Annisa Al-Isra; Sunarsih; Dea Ayu Sapitri; Mutiara Kurnia Sari; Quina; Raden Azty Afifadyandi; Afifah Indah Sari; Ade Rizki; Sintya Merinda; Faizah Nurul Aliyah; Pipit Kun Maya; Ayi S. Ruqayyah; Kasiyanti (CV. Doki Course and Training, 2023)
This study aims to determine how the level of confidence for physical disabilities by the Islamic psychotherapy approach at the Budi Perkasa Sentra Palembang. The research method used is the method of qualitative research with a phenomenological approach. Subjects in research are two people (adults) with physical disabilities in the Budi Perkasa Sentra of N (male) and H (female). Methods of data collection using interviews, observation, and documentation. The results of this study conclude that subjects are able to accept their current conditions, in the sense of no inferiority or embarrassment of the limitations of possession. Subjects have good confidence, they are aware of the disadvantages they have, but they are also aware of the excess tucked inside themselves are aware of the disadvantages they have, but they are also aware of the excess tucked in themselves. Factors that affect the sense of confidence is because social support that always encourages and encourages them in every situation, and also they believe and represent Allah SWT, they believe that every human being is inseparable from excess and disadvantage.